Descripción agronómica y matemática de algunos sistemas de poda de Coffea arabica en Centro América, México y República Dominicana - Somarriba, E.; Quesada, F.; López Sampson, A.; Melo, E.D.; Medina, B.; Muschler, R.; Chaves, V.; Martínez, R. (Centro Agronómico Tropical de Investigación y Enseñanza, 2021)
This manual is aimed at agronomists, researchers and extensionists dedicated to the development of new ways of managing the vegetative and productive tissue of coffee through pruning. Here, we provide a technical-mathematical tool that helps in the conceptualization of the development of tissues subjected to pruning and its relationship with the yield of coffee beans, per plant and per area. In this manual we concentrate on the demographic and productive aspects of coffee plants and briefly present the mathematical foundations behind the models, which are presented in another publication (Somarriba et al. 2021).